Targeted muscle reinnervation in oncologic amputees: Early experience of a novel institutional protocol. Issue 3 (13th June 2019) - Alexander, John H.; Jordan, Sumanas W.; West, Julie M.; Compston, Amy; Fugitt, Jennifer; Bowen, J. Byers; Dumanian, Gregory A.; Pollock, Raphael; Mayerson, Joel L.; Scharschmidt, Thomas J.; Valerio, Ian L.
Abstract: Background: We describe a multidisciplinary approach for comprehensive care of amputees with concurrent targeted muscle reinnervation (TMR) at the time of amputation. Methods: Our TMR cohort was compared to a cross‐sectional sample of unselected oncologic amputees not treated at our institution (N = 58). Patient‐Reported Outcomes Measurement Information System (NRS, PROMIS) were used to assess postamputation pain. Results: Thirty‐one patients underwent amputation with concurrent TMR during the study; 27 patients completed pain surveys; 15 had greater than 1 year follow‐up (mean follow‐up 14.7 months). Neuroma symptoms occurred significantly less frequently and with less intensity among the TMR cohort. Mean differences for PROMIS pain intensity, behavior, and interference for phantom limb pain (PLP) were 5.855 (95%CI 1.159‐10.55; P = .015), 5.896 (95%CI 0.492‐11.30; P = .033), and 7.435 (95%CI 1.797‐13.07; P = .011) respectively, with lower scores for TMR cohort. For residual limb pain, PROMIS pain intensity, behavior, and interference mean differences were 5.477 (95%CI 0.528‐10.42; P = .031), 6.195 (95%CI 0.705‐11.69; P = .028), and 6.816 (95%CI 1.438‐12.2; P = .014), respectively. Fifty‐six percent took opioids before amputation compared to 22% at 1 year postoperatively. Conclusions: Multidisciplinary care of amputees including concurrent amputation and TMR, multimodal postoperative pain management, amputee‐centered rehabilitation, and peer support demonstrates reduced incidence and severity of neuroma and PLP.